Pengaruh Pupuk Kotoran Ayam Terhadap Pertumbuhan Dan Hasil Jahe Pada Tanah Aluvial - -, Misnadeh (Jurnal Sains Pertanian Equator, 2019)
Productivity of ginger (Zingiber officinale) in Indonesia are generally low, this may be related to several factors such as less optimal fertilization, unsuitable environmental conditions to grow, both climate and soil fertility, as well as the use of non recommended cultivation techniques. The aims of this study was to determine the effect of Cattle Chicken Manures on The Growth and Yield of Ginger on alluvial soil. The experiment was conducted at the from April until Juni 2018. The research design used in this study was Completely Randomized Design with 5 levels Cattle Chicken Manures The treatments were the use of P1 = 10 ton/ha , P2 = 15 ton/ha, P3 = 20 ton/ha, P4 = 25 ton/ha, P5 = 30 ton/ha. Each treatment was repeated five times, and the experimental unit consisted of 4 plant samples. Varieties of ginger used came from farmer"™s garden. The parameters measured were plant height, number of tillers, number of leaves, number of klorofil and rhizome weight plant-1. The results showed that Peel have significant effect on plant height, number of tillers, number of leaves, number of klorofil and rhizome weight plant. Result of diversity in this research showed that 20 ton/ha Peel equal of 2,8 kg/ha give tend better than dose another treatment toward to ginger plant and yield on alluvial soil.Keywords: Aluvial, Chicken manures, Ginger